Gluten Introduction and the Risk of Coeliac Disease: A Position Paper by the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition. Issue 3 (March 2016) - Szajewska, Hania; Shamir, Raanan; Mearin, Luisa; Ribes-Koninckx, Carmen; Catassi, Carlo; Domellöf, Magnus; Fewtrell, Mary S.; Husby, Steffen; Papadopoulou, Alexandra; Vandenplas, Yvan; Castillejo, Gemma; Kolacek, Sanja; et al.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background: The European Society for Paediatric Gastroenterology, Hepatology and Nutrition recommended in 2008, based on observational data, to avoid both early (<4 months) and late (≥7 months) introduction of gluten and to introduce gluten while the infant is still being breast-fed. New evidence prompted ESPGHAN to revise these recommendations. Objective: To provide updated recommendations regarding gluten introduction in infants and the risk of developing coeliac disease (CD) during childhood. Summary: The risk of inducing CD through a gluten-containing diet exclusively applies to persons carrying at least one of the CD risk alleles. Because genetic risk alleles are generally not known in an infant at the time of solid food introduction, the following recommendations apply to all infants, although they are derived from studying families with first-degree relatives with CD. Although breast-feeding should be promoted for its other well-established health benefits, neither any breast-feeding nor breast-feeding during gluten introduction has been shown to reduce the risk of CD. Gluten may be introduced into the infant's diet anytime between 4 and 12 completed months of age. In children at high risk for CD, earlier introduction of gluten (4 vs 6 months or 6 vs 12 months) is associated with earlier development of CD autoimmunity (defined as positive serology) and CD, but the cumulative incidence of each in later childhood is similar. Based on observational data pointing to the association between the amount of gluten intake and risk of CD, consumption of large quantities of gluten should be avoided during the first weeks after gluten introduction and during infancy. The optimal amounts of gluten to be introduced at weaning, however, have not been established.